Battle of Attu and the Aleutian Island Campaign. - Metcalf, Matthew Scott (Fort Leavenworth, KS : US Army Command and General Staff College, 2014)
The Battle of Attu is a case study for the importance of the proper application of operational art into the planning and preparation of a major military operation. This monograph provides a succinct historical account of the events surrounding the Battle of Attu and the Aleutian Island Campaign in order to provide the strategic and operational context that shaped the American operational approach. Analysis of primary source data used includes personal accounts, media sources, and previous studies. America was successful due to its ability to organize and apply combat power by leveraging the elements of operational art; specifically, the elements of operational reach and basing. These elements led to the building of depth during the Battle of Attu which was critical to the successful outcome of the battle.